Underestimation of money growth and pensions: Experimental investigations - Féidhlim P. McGowan; Pete Lunn; Deirdre A. Robertson (The Economic and Social Research Institute (ESRI), 2019)
People underestimate long-term growth in savings because they linearise exponential growth - a phenomenon known as exponential growth bias (EGB). This bias has implications for multiple financial decisions, particularly those relating to pensions. We hypothesised that underestimation might be even more severe for regular savings relative to lump sums, because savers need also to estimate accumulation. The additional cognitive load could strengthen EGB, or individuals might underestimate accumulation in addition to EGB. Four experiments investigated: (1) whether underestimation of money growth is greater for long streams of regular savings than for lump sums; (2) whether underestimation occurs when questions are framed intuitively as the cost of delaying starting a pension; and (3) whether practice with a calculator designed to illustrate the cost of delay attenuates underestimation. Individuals were more likely to underestimate money growth from regular savings than from lump sums, because they failed to accumulate contributions in addition to displaying EGB. Underestimation was substantial and persistent. Practice with a calculator partially attenuated underestimation, primarily among individuals with higher educational attainment and without a pension. Overall, these findings imply that across multiple judgements, decisions and frames, individuals substantially underestimate money growth, reducing the attractiveness of saving.
Keywords: 330